Influence of Employee Mindfulness on Work Engagement with Self-Efficacy as a Mediator - Yolanda Adrima; Mega Asri Zona (SAFE-Network, 2026)
This study aims to analyze the effect of employee mindfulness on work engagement with self-efficacy as a mediating variable in Bank Nagari Padang employees. This study uses a quantitative approach with a survey method, where data were collected from 159 respondents through questionnaires and analyzed using the Partial Least Squares-Structural Equation Modeling method. The results of the study indicate that employee mindfulness has a positive and significant effect on work engagement, employee mindfulness has a positive and significant effect on self-efficacy, self-efficacy has a positive and significant effect on work engagement, and self-efficacy is able to mediate the effect of employee mindfulness on work engagement. This study is supported by Job Demands-Resources Theory which explains that personal resources owned by individuals, such as employee mindfulness and self-efficacy, can increase work motivation and employee engagement in work. In addition, Conservation of Resources Theory explains that individuals who have good psychological resources tend to be able to develop other resources, resulting in more positive work conditions. In this study, employee mindfulness helps increase employee self-efficacy, which ultimately encourages increased work engagement among Bank Nagari Padang employees.